PENGARUH KECEMASAN TERHADAP TEKANAN DARAH PADA LANSIA DENGAN RIWAYAT HIPERTENSI: STUDI CROSS-SECTIONAL - Qodir, Abdul; Pomalingo, Sitti Fizraini; Muntaha, Muntaha (Jurnal Ilmiah Kesehatan Media Husada, 2026)
Anxiety is an important factor that may affect blood pressure in the elderly, where the stress response triggered can worsen health conditions by increasing blood pressure through sympathetic nervous system hyperactivity. Analyzing the effect of anxiety on blood pressure in the elderly in the working area of ​​the Ardimulyo public Health Center work area, Malang Regency. This study used a cross-sectional design, conducted at the Ardimulyo Health Center in Malang Regency. The sampling technique employed was purposive sampling with a sample size of 60. The instruments used were the Geriatric Anxiety Scale (GAS) questionnaire and a digital blood pressure meter. The analysis was conducted using the Kruskal-Wallis test and the Post Hoc Mann-Whitney test. The results of this study on anxiety showed that 2 individuals (3.3%) fell into the non-anxious category, 24 individuals (40.0%) experienced mild anxiety, 31 individuals (51.7%) had moderate anxiety, and 3 individuals (5.0%) had severe anxiety. For systolic blood pressure in mmHg, the mean was 143.2 mmHg, with a minimum of 105 mmHg, a maximum of 189 mmHg, and a standard deviation of 20.97 mmHg. The mean diastolic blood pressure was 82.68 mmHg, with a minimum of 62 mmHg, a maximum of 156 mmHg, and a standard deviation of 12.931 mmHg. The results of the Kruskal-Wallis test for systolic blood pressure indicated a p-value <0.05 (p < 0.001), and for diastolic blood pressure, the p-value was <0.05 (0.017). The Post Hoc Mann-Whitney test for systolic blood pressure showed a significant difference between mild anxiety and moderate anxiety, with a p-value <0.05 (p < 0.001), while the diastolic blood pressure showed a significant difference between mild anxiety and severe anxiety, with a p-value <0.05 (0.013). There is a significant effect of anxiety on systolic blood pressure and diastolic blood pressure.